ÖZEL YETENEKLİ ÖĞRENCİLERİN PROGRAMLAMA DİLİ ÖĞRETİMİNDE KODU GAME LAB YAZILIMININ PROBLEM ÇÖZME BECERİLERİ DÜZEYİNE ETKİSİ. - ALKAN, Ayşe (Mehmet Akif Ersoy University Journal of Education Faculty, 2019)
In the 21st century, basic skills such as critical thinking, problem solving, analyzing and synthesizing, working collaboratively, being innovative and productive, easy access to accurate and up-to-date information are expected. The rapid developments in science and technology in gaining the skills expected from 21st century students have an important place in the process of creating desired behavior change in individuals. One of the main features of the programming course is to provide students with the skills of algorithmic thinking and solving problems encountered. The aim of this study is to reveal the effect of this environment on students' problem solving skills by using Code Game Lab 3D software development environment in programming language teaching. The study group of the study consisted of 35 students studying in the 5th grade in the 2017-2018 academic year in the province of Samsun. Screening model was used in the research. Problem Solving Inventory for Children problem developed by Serin, Bulut Serin and Saygılı (2010) was used to reveal the change in problem solving skills before and after the application of the data. The data obtained by quantitative data collection tools were analyzed by using SPSS 22 statistical program and the level of significance was accepted as .05 in all analyzes. In addition to descriptive statistics, T test was used to analyze the quantitative data. As a result of the research, it was seen that coding education has a positive effect on problem solving skills of special talented students.